1991
DOI: 10.1099/00221287-137-11-2649
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the force necessary for removal of bacterial cells from a quartz plate

Abstract: The force necessary to remove the cells of a bacterium, an isolate (Bacillus sp.) from grassland soil, from a quartz plate was investigated in phosphate buffer solution by using a well-defined liquid flow caused by electroosmosis. The cells were not removed at a specific strength of removal force but removed over a wide range of force, about 10-14-10-12 N per cell. An exponential relation was observed between the removal force and the number of removed cells in media of pH 7.0,8.0 and 9.0; more cells were remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 12 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…A small amount of bacterial suspension (25-50 j l) in 10 mM NaCI was added to 10 mM PBS (5-10 ml) to a concentration of 10' cells/ml. The EPM Charge of Soil Bacteria 67 of the isolates was determined at the upper stationary level of a flat rectangular quartz cell (Rank Brothers, UK) submerged in a water bath (25°C) as previously reported (11). To estimate the reproducibility of the experiments, the measurement of EPM was repeated for two cultures of the same isolate: 12 strains were examined at different pHs; the mean of standard errors of these measurements was 0.19 x 10-8 m2 V -1 s -1.…”
Section: Methodsmentioning
confidence: 99%
“…A small amount of bacterial suspension (25-50 j l) in 10 mM NaCI was added to 10 mM PBS (5-10 ml) to a concentration of 10' cells/ml. The EPM Charge of Soil Bacteria 67 of the isolates was determined at the upper stationary level of a flat rectangular quartz cell (Rank Brothers, UK) submerged in a water bath (25°C) as previously reported (11). To estimate the reproducibility of the experiments, the measurement of EPM was repeated for two cultures of the same isolate: 12 strains were examined at different pHs; the mean of standard errors of these measurements was 0.19 x 10-8 m2 V -1 s -1.…”
Section: Methodsmentioning
confidence: 99%
“…The D 99.9 value represents the point at which 0.1% of the microbial cells remained on the substratum. Morisaki [50] measured the force necessary to remove the cells of Bacillus sp. from a quartz plate in phosphate buffer using a liquid flow caused by electroosmosis, and demonstrated that the cells were not removed at a specific strength of removal force but removed over a wide range of force.…”
Section: Microbial Attachment On the Glass Surfacementioning
confidence: 99%
“…However, when fluid flow exceeds a critical limit (49), resulting wall shear rates may become high enough to prevent adhesion (65,78) or even stimulate detachment. For instance, in aqueous suspensions, wall shear rates of 6,000 to 8,000 s Ϫ1 (equivalent to shear forces of between 6 ϫ 10 Ϫ3 and 8 ϫ 10 Ϫ3 nN) were sufficient to prevent adhesion of Pseudomonas fluorescens to stainless steel, while wall shear rates of 12,000 s Ϫ1 (or shear forces of 12 ϫ 10 Ϫ3 nN) could detach adhering organisms (78).…”
Section: Introductionmentioning
confidence: 99%